Public artworks and the freedom of panorama controversy: a case of Wikimedia influence - Mélanie Dulong de Rosnay; Pierre-Carl Langlais (Internet Policy Review)
Freedom of panorama, an exception to copyright law, is the legal right, in some countries, to publish pictures of artworks which are in public space. A controversy emerged at the time of the discussions towards the revision of the 2001 European Copyright Directive, opposing free knowledge communities as advocates of the public domain, and authors’ collecting societies aiming at preserving their constituents’ income. The article decrypts the legal framework and political implications of a topic which has been polarising copyright reform lobbyists, and analyses its development within the public debate since the XIXth century. Articulating legal analysis with text mining, this article aims at contributing to the policy debate.